Mutations in rpoB and fusA cause resistance to rifampicin and fusidic acid in methicillin-resistant Staphylococcus aureus strains from a tertiary hospital in Malaysia - Lim, K.T.; Teh, C.S.J.; Mohd Yasim, M.Y.; Thong, Kwai Lin (Oxford University Press, 2013)
Abstract